2010
DOI: 10.1002/maco.200905442
|View full text |Cite
|
Sign up to set email alerts
|

330Cb alloy (Fe35Ni18Cr1Nb2Si) oxidation study between 800 and 1000 °C

Abstract: The 330Cb alloy (Fe-35Ni-18Cr-1Nb-2Si) has been oxidized, in air, in the 800-1000 8C temperature range. Results show the formation of a chromia layer acting as a good diffusion barrier under isothermal conditions. Nevertheless, some oxide scale spallation is generally observed after cooling to room temperature. A fine and adherent chromia scale is only obtained after short-term oxidation at 800 8C. In this case, the scale is probably too fine to expect a protection against carburization. At 900 8C we have obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…A recent paper has discussed the niobium and silicon effects on a 330Cb austenitic steel high temperature oxidation [36]. Its influence was negligible on the oxidation process but it was observed, that silicon and niobium have a good affinity to each other.…”
Section: Niobium and Silicon Influence On High Temperature Oxidationmentioning
confidence: 96%
“…A recent paper has discussed the niobium and silicon effects on a 330Cb austenitic steel high temperature oxidation [36]. Its influence was negligible on the oxidation process but it was observed, that silicon and niobium have a good affinity to each other.…”
Section: Niobium and Silicon Influence On High Temperature Oxidationmentioning
confidence: 96%
“…Then chromia‐forming alloys with additional silicon are used. However, former studies have shown that the oxidation in air leads to a poorly adherent chromia scale and did not permit a continuous silica scale formation even though the alloy contains about 2 wt% silicon . One way to act on the oxide scale formation consists of modifying the gaseous environment, using inert gases .…”
Section: Introductionmentioning
confidence: 99%
“…However, former studies have shown that the oxidation in air leads to a poorly adherent chromia scale and did not permit a continuous silica scale formation even though the alloy contains about 2 wt% silicon. [4][5][6] One way to act on the oxide scale formation consists of modifying the gaseous environment, using inert gases. [7] Previous works have shown that, on an austenitic steel, a protective silica scale formation is promoted by low-oxygen gaseous environments and a high-alloy silicon content.…”
Section: Introductionmentioning
confidence: 99%
“…The HR‐120 alloy showed the poorest cyclic‐oxidation resistance, due to bad scale adhesion and the tendency of iron (33 wt%) to oxidize. Former studies have shown that the oxidation of the AISI 330Cb alloy at 900°C in the air lead to a poorly adherent chromia scale and did not permit a continuous silica scale formation even though the alloy contains about 2 wt% silicon . Then, the protection against corrosive environments was not ensured.…”
Section: Introductionmentioning
confidence: 99%
“…Former studies have shown that the oxidation of the AISI 330Cb alloy at 900°C in the air lead to a poorly adherent chromia scale and did not permit a continuous silica scale formation even though the alloy contains about 2 wt% silicon. [7][8][9] Then, the protection against corrosive environments was not ensured. One way to act on the oxide scale formation consists in modifying the gaseous environment, using inert gases.…”
Section: Introductionmentioning
confidence: 99%